Variability in the drinking behaviour of individual emus dromaius novaehollandiae - Davies, Stephen; Knight, T. (CSIRO Publishing, 2016)
The drinking behaviour of four captive emus Dromaius novaehollandiae Latham 1790 was examined at the CSIRO Laboratory, Helena Valley, Western Australia. Considerable individual variation was found in the amount of water each emu drank daily, but for each bird the amount drunk was positively correlated with daily ambient maximum temperature. There was also considerable variation between individual birds in the number of sips of water taken daily, in the mean size of each sip and in the distribution of the size of sips taken in each drinking bout. Variability in drinking behaviour has been reported in other species of bird when their water influx has been calculated using double-labelled water. The availability of water to emus varies greatly in both time and space. More thirsty emus may do well when water is plentiful, whereas more abstemious ones may be favoured when water is scarce. Hence, variability in drinking behaviour would be maintained in populations.